Updated Swedish guidelines for the management and treatment of RSV infection - Navér, Lars; Andersson, Emmi; Blomgren, Frida; Ljungberg, Henrik; Luthander, Joachim; Nordlander, Anna; Odermarsky, Michal ; 0000-0002-0852-5691; Ohlin, Andreas; Rhedin, Samuel; Schollin Ask, Lina; Strömdahl, Susanne; Swartling, Lisa; et al. (Infectious Diseases, 2025)
In May 2024 with a subsequent update in June 2025, the Swedish Medical Products Agency’s expert group revised guidelines on the management and treatment of respiratory syncytial virus (RSV) infection. This is an abridged version and commentary on the full recommendation including specific recommendations for the RSV-season 2025/2026. Key points are: (i) RSV is a seasonal, highly contagious infection. Almost all children are infected by age two, usually with mild illness; (ii) Some infants, children with underlying conditions, and frail elderly are at risk for developing severe disease requiring hospital care; (iii) Preventive measures—such as hand hygiene and avoiding contact with people with colds—are essential to protect infants and the elderly; (iv) Prophylactic treatment with monoclonal antibodies reduces the risk of infants developing severe RSV disease and requiring hospital care. The long-acting drug nirsevimab is preferred over the shorter-acting palivizumab; (v) Universal prophylaxis in infants reduce disease burden for both families and society; (vi) If supply is limited, children at highest risk should be prioritised for prophylaxis; (vii) Maternal vaccination during pregnancy lowers the risk of severe RSV in newborns, decreasing hospital admissions. The protective effect is considered to be equivalent to that of monoclonal antibodies. Recommendations and funding decision for maternal vaccination is under investigation during the autumn of 2025; (viii) In the elderly, vaccination is the most effective pharmacological prevention; (ix) There is no effective antiviral treatment for established RSV disease; management is symptomatic and supportive. Hospitalised children should not be subjected to measures with no proven effect, preferable minimal interventions, with treatment focused on ensuring adequate nutrition; (x) The Swedish recommendations state that during the RSV season 2025/2026, nirsevimab should be administered to prevent RSV infection in all infants aged 0–3 months during the RSV season and to infants under 12 months with increased risk of severe RSV and certain high risk children under 24 months.
doi: 10.1080/23744235.2025.2580945